Effects of sacubitril/valsartan on functional status and exercise capacity in real-world patients. Issue 5 (3rd September 2019) - Lau, Chirik Wah; Martens, Pieter; Lambeets, Seppe; Dupont, Matthias; Mullens, Wilfried
Abstract: Background: Sacubitril/valsartan significantly reduced heart failure(HF) hospitalisations and mortality in the PARADIGM-HF-trial. However real-world data on symptomatic and functional improvement are lacking. Methods: Between December 2016 and January 2018, we retrospectively collected baseline and follow-up data including New York Heart Association (NYHA)-functional class and Cardio-pulmonary exercise data(CPET) in all HF-patients receiving sacubitril/valsartan. Additionally, in patients with an implantable electric cardiovascular device (IECD) enrolled in remote telemonitoring, we quantified patient level activity before and after initiation. Results: A total of 201 patients (82% males) were identified. NYHA-functional class was reassessed after an average of 221 ± 114 days. Overall, 3.3% of patients improved 2 NYHA classes, 28.7% improved 1 NYHA class, 64% remained stable and 4% deteriorated 1 NYHA class. Patients with symptomatic improvement exhibited a larger reduction in Left Ventricular End Systolic Volume(LVESV) and a larger increase in Left Ventricular Ejection Fraction(LVEF[ p -value both <.05]). In total, 110 patients (55%) were equipped with an IECD capable of quantifying outpatient activity-level. On an average of 364 days before sacubitril/valsartan, an activity expressed as %-of-the-day was 13 ± 2%, vs. 18 ± 3% the 364 days following sacubitril/valsartan initiation. Signifying a 38% improvement in the out-patient activity level. CPET-data was obtained in paired-fashion in 45 patients (22%). VO2max at baseline (14.7 ± 3.8 mL/kg/min) did not significantly change at follow-up (14.1 ± 4.7 mL/min/kg; p = .237). Conclusion: Real-world patients exhibit significant symptomatic and functional improvement following the initiation of sacubitril/valsartan. However, larger prospective studies are necessary to assess the impact of sacubitril/valsartan on indices of maximal exercise performance measured during CPET.